1982
DOI: 10.1007/bf00213864
|View full text |Cite
|
Sign up to set email alerts
|

Development of the tympanal organ in larvae of the migratory locust (Locusta migratoria)

Abstract: The tympanal organ of the migratory locust acquires its definitive form during larval development. All the receptor cells (90-100) are present in the 1st instar, whereas the differentiation of the tympanum and the cuticular structures it bears proceeds in steps from one instar to the next. The elevated process is the earliest such structure to appear (2nd instar); it is followed by the pyriform vesicle (3rd instar) and folded body (4th instar). The styliform body first appears in the imago. Although the typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 1 publication
0
29
0
Order By: Relevance
“…Ligament scolopales are only those in the ligament attaching to the tympanumgenerally the easiest and most consistent counts. No data were collected pattern seen in acridids (Michel and Petersen, 1982;Petersen et al, 1982;Boyan, 1983) but is quite different from that reported for crickets (Ball and Young, 1974;Ball and Hill, 1978;Ball et al, 1989).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Ligament scolopales are only those in the ligament attaching to the tympanumgenerally the easiest and most consistent counts. No data were collected pattern seen in acridids (Michel and Petersen, 1982;Petersen et al, 1982;Boyan, 1983) but is quite different from that reported for crickets (Ball and Young, 1974;Ball and Hill, 1978;Ball et al, 1989).…”
Section: Discussionmentioning
confidence: 62%
“…Among the tympanate insects with incomplete metamorphosis (hemimetabolous), locust auditory development has received the most attention (Michel and Petersen, 1982;Petersen et al, 1982;Boyan, 1983;Breckow and Sippel, 1985;Meier and Reichert, 1990) followed by that of crickets (Ball and Young, 1974;Ball and Cowan, 1978;Ball and Hill, 1978;Ball et al, 1989) and tettigoniids (Meier and Reichert, 1990). No comparable published reports currently exist for insects with complete metamorphosis (holometabolous).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…After the locust emerges as an adult, some cuticle features continue to harden and sclerotize (Uvarov, 1966). The locust ear is not fully developed until it reaches its adult form (Michel and Petersen, 1982). Additionally, the maturation period of females varies with environmental condition; for example, lush versus dry plants affect the time that Schistocerca gregaria take to lay their first egg pod with a range of 33 to 54 days, respectively (Uvarov, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…These changes in connectivity provide a mechanism to maintain interneuron response properties through different instars, which is needed because the number of hair sensilla increases by as much as a factor of 10 from hatching to adulthood and because the mechanical properties alter as the size of individual sensilla increases (Anderson and Bacon, 1979;Newland et al, 1995;Pflüger et al, 1994). In contrast, the locust ear already has the adult complement of auditory receptors at hatching (Michel and Petersen, 1982).…”
Section: Introductionmentioning
confidence: 99%